(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1911)
A report on the excavation of a newly discovered hut circle. The walls were composed of stones laid on sandy soil and survived to a height of one and a half feet. The thickness of the wall was irregular. Two doorways and a stone floor were revealed. A small paved passageway led up to one of the doors. Outside the wall of the hut-circle, and to the left of the entrance, a small chamber completely walled in was found. A few animal bones, shells, two iron objects and a bone pin were recovered during the excavation.